[OP.7B.08] INFLUENCE OF GENDER ON THE RELATIONSHIPS BETWEEN NEW INDICES OF ADIPOSITY AND LEFT VENTRICULAR MASS AND HYPERTROPHY IN HYPERTENSIVE PATIENTS. (September 2016) - Mulè, G.; Castiglia, A.; Schillaci, M.K.; Luna, C.; Morreale, M.; Geraci, G.; Altieri, D.; Calandra, L.; Cottone, S.; Nardi, E.
Abstract : Objective: The unfavourable effects of the association of obesity with hypertension on cardiac structure and function have been extensively studied. However, controversy still exists about the influence of gender on the relationship between obesity and left ventricular mass (LVM) and hypertrophy (LVH). Even if body mass index (BMI) and waist circumference (WC) are widely used as anthropometric predictors for cardiovascular diseases (CVD), their validity has been questioned. Recently, Body Shape Index (ABSI) and Body Roundness Index (BRI) were proposed as alternative measures of adiposity that may better reflect health status (1–2). Our study was aimed to assess the ability of ABSI and BRI in identifying LVH and to determine whether they are superior to BMI and WC. Moreover, the influence of gender on the relationships between all these indices of adiposity and LVM was also evaluated. Design and method: We enrolled 724 subjects with EH (mean age 45 ± 12 years, 63 % men) without cardiovascular complications. In all subjects the anthropometric indices (weight, height and waist circumference) and the routine biochemical parameters were determined. BMI, ABSI and BRI were calculated. Furthermore, all patients underwent a 24-h blood pressure monitoring and an echocardiogram. LVM was indexed for body surface area (LVMI) and for height2.7 (LVMH2.7). Results: The univariate correlations of LVMI and LVMH2.7 with the measures of adiposity evaluated are shown in the table 1. ROC curves analysis revealed that in overall population (table 2) and in men BRI has a greater ability to identify LVH defined as LVMH2.7 > 51 g/m2.7. Figure. No caption available. Conclusions: Our results seems to suggest that in men, but not in women, the BRI has a greater sensitivity to detect LVH than ABSI and the traditional measures of adiposity.